TỔNG HỢP CAO SU THIÊN NHIÊN LỎNG CÓ NHÓM HYDROXYL CUỐI MẠCH BẰNG PHƯƠNG PHÁP FENTON QUANG HOÁ 1. NGHIÊN CỨU ẢNH HƯỞNG CỦA CÁC ĐIỀU KIỆN PHẢN ỨNG FENTON QUANG HOÁ - Lý, Phạm Hữu; Bích Thanh, Đỗ Thị; Hồng, Kim Thuý; Giang, Lê Đức (Vietnam Journal of Science and Technology, 2012)
SUMMARY Some reaction conditions of the Photo Fenton process to prepare hydroxyl-terminated liquid natural rubber (LNR-OH), such as pH, H2O2/Fe2+ ratio, reaction time, reaction temperature, initial concentration of natural rubber (NR) have been investigated in detail. It was shown that at pH 3, H2O2/Fe2+ ratio 1,5, concentration of NR 5%, T 35 oC the Photo Fenton process took place the best resulting in the formation of LNRs-OH, that have Mv 4,500 and 3,800 after 80 h and 100 h, respectively. Keywords. liquid natural rubbers, Fenton reaction, hydroxyl-terminated liquid natural rubbers